(untitled) (Research, Society and Development, 2020)
This study aimed to identify care related to expressive actions relevant to the care management of patients with chronic venous ulcers. This is a methodological study developed with 30 participants, with the research field being the virtual environment. The collection took place from august to december 2018, through the form of identification data of the research participants and the script for identifying care for people with chronic venous ulcers. The results showed that the expressive actions that guide the care of patients with venous ulcers are related to psychological and social aspects, measures to prevent recurrences, health and religiosity / spirituality guidelines. In view of the above, it is concluded that the expressive actions provide subsidies for the management of care, valuing a more humanized care, based on the real needs of the assisted subject, with a view to promoting actions that are not restricted to the biological spheres, but that pass through the spheres psychosocial and spiritual, promoting the rupture of the cartesian model.